Rasionalitas Pelaku Usaha Pangan dalam Mengajukan Sertifikasi Halal: Perspektif Kesadaran, Literasi, dan Regulasi - Fitriyanto, Doni; Abin, Moh. Rois; Maulana, Moch. Hafiz (Universitas Islam Kadiri, 2026)
This study examines the rationality of food business actors in deciding to apply for halal certification. Although halal certification has become a regulatory requirement for food products in Indonesia, the decision to obtain certification is often shaped by multiple considerations beyond formal compliance. This research aims to explore how halal awareness, halal literacy, and regulatory support influence the decision-making process of food entrepreneurs in applying for halal certification. A qualitative approach was employed using semi-structured interviews with seven food business actors who had applied for halal certification. Data were analyzed through thematic interpretation to identify patterns of reasoning underlying their decisions. The findings reveal that the decision to apply for halal certification is formed through a layered rationality process involving moral awareness, cognitive understanding of certification procedures, and institutional encouragement through government programs and regulations. Halal awareness acts as the initial moral driver that shapes entrepreneurs’ orientation toward responsible food production, while halal literacy reduces uncertainty and enables practical engagement with the certification process. Regulatory support, including facilitation programs and technical assistance, further reinforces this decision by lowering administrative and financial barriers. The study concludes that halal certification should be understood not merely as a regulatory obligation but as a strategic business decision shaped by the interaction of ethical values, knowledge capacity, and institutional frameworks.